Features of the structure active centers of industrial catalysts for the oxidative chlorination of ethylene - Kurta, Sergiy; Mykytyn, Ihor; Ribun, Victoria; Khatsevich, Olga (International Journal of Engineering and Technology, 2018)
The active phase of CuCl2, HÐ¡uÐ¡l2, H2Ð¡uÐ¡l4 and two grades of industrial ethylene oxidation chlorination catalysts (EOC) such as deposited catalyst X1 (Harshow), with copper chlorides supported on an alumina surface, and a permeated MEDC-B catalyst immobilized in the internal pores of the firm of the company Sud-Chemie. Catalyst were analyzed by the method of thermoemission electronic raster (VEGA3NTSCAN) microscopy and X-ray fluorescence energy dispersion spectroscopy (EDX-7000). It is shown that the active catalyst centers of CuCl2 have different crystalline structure from the amorphous active phase of H2CuCl2, H2CuCl4 on the surface of the catalysts. On the surface of X1 Harshow copper chlorides are uniformly distributed throughout the volume of the carrier catalyst Î³-Al2O3 in the form of amorphous portions [CuCl4]-2, [CuCl2]-1. At the same time, on the surface of the catalyst MEDC-B, the active centers have a separate cluster immobilized crystalline structure of the active phase, which differs from the composition of the carrier Î³-Al2O3.Â Â